Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

Green manuring outperforms cattle manure in soil carbon sequestration by reshaping dissolved organic matter composition and fungal life strategies - Siwei Shi; Songjuan Gao; Guopeng Zhou; Danna Chang; Rui Liu; Ting Liang; Jiudong Zhang; Zongxian Che; Weidong Cao (Soil and Tillage Research, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Using ethylene combined with green manuring to enhance rice productivity, economic benefit, and energy efficiency in double-rice paddy field - Jinxin Sun; Guopeng Zhou; Danna Chang; Rui Liu; Han Liu; Zhengbo Ma; Ting Liang; Jia Liu; Chunqin Zou; Weidong Cao (Field Crops Research, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

A comprehensive strategy for solving Cd risk while improving soil quality and rice yield in paddy fields: Co-utilizing green manure, rice straw, and biochar - Ting Liang; Danna Chang; Guopeng Zhou; Cheng Cai; Rui Liu; Jinxin Sun; Songjuan Gao; Zhengbo Ma; Jiancheng Xie; Siwei Shi; Jun Nie; Yulin Liao; et al. (Journal of Hazardous Materials, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Ethylene stimulates methane oxidation and inhibits methane production in green manure-rice systems - Jinxin Sun; Zhengbo Ma; Guopeng Zhou; Ting Liang; Rui Liu; Danna Chang; Han Liu; Jia Liu; Chunqin Zou; Weidong Cao (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Oreonectes yuedongensis (Cypriniformes, Nemacheilidae), a new freshwater fish species from the Lianhua Mountains in eastern Guangdong, China - Chang‐Ting Lan; Tao Luo; Xin‐Rui Zhao; Jing Yu; Ning Xiao; Jiang Zhou (Journal of Fish Biology, 2024)
In this work, we describe a new species of the genus Oreonectes , Oreonectes yuedongensis sp. nov., collected from the Lianhua Mountains in eastern Guangdong, China. Phylogenetic trees constructed based on the mitochondrial cytochrome b ( Cyt b ) gene showed that this new species represents an independent evolutionary lineage, with uncorrected genetic distances (Kimura 2‐parameter model) from congeners ranging from 5.1% to 8.3%. In addition, nuclear DNA analysis indicated O. yuedongensis as an independent lineage separate from its closely related species. Morphologically, the new species can be distinguished from other six species in the genus Oreonectes by a combination of serial characters. The description of this new species suggests that it is necessary to reassess the biodiversity of Oreonectes platycephalus as a complex, especially in the middle reaches of the Pearl River near the border between Guangdong and Guangxi. Morphological and genetic evidence supports O. yenlingi as a synonym of O. platycephalus .

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Reductive stress induced by NRF2/G6PD through glucose metabolic reprogramming promotes malignant transformation in Arsenite-exposed human keratinocytes - Qianlei Yang; Rui Yan; Jie Zhang; Ting Zhang; Qi Kong; Xiaoyun Zhang; Haixuan Xia; Aojun Ye; Xinhua Qiao; Koichi Kato; Chang Chen; Yan An (Science of The Total Environment, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Comparison of thermal alkaline pretreatment and zinc acetate-catalyzed methanolysis (MtOH-ZnOAc) for anaerobic digestion of bioplastic waste - Jayen Aris Kriswantoro; Chen-Yeon Chu; Ting-Rui Chang; Hao-Jen Pai; Chih-Kai Chang; Yi-Pang Chiu (Bioresource Technology, 2023)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Co-incorporating leguminous green manure and rice straw drives the synergistic release of carbon and nitrogen, increases hydrolase activities, and changes the composition of main microbial groups - Guopeng Zhou; Danna Chang; Songjuan Gao; Ting Liang; Rui Liu; Weidong Cao (Biology and Fertility of Soils, 2021)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Candidate gene prediction via quantitative trait locus analysis of fruit shape index traits in apple - Ke Cao; Yuansheng Chang; Rui Sun; Fei Shen; Ting Wu; Yi Wang; Xinzhong Zhang; Zhenhai Han (Euphytica, 2015)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)